2018
DOI: 10.14419/ijag.v6i1.9791
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals with ecological risk of soils in the industrial vicinity of Tangail district, Bangladesh

Abstract: This study was conducted to assess the ecological risk of heavy metals in soils collected from the industrial vicinity of Tangail district in Bangladesh. In this study, the levels of six heavy metals namely chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd), and lead (Pb) in 15 sampling sites around the industrial vicinity of Tangail district in Bangladesh were assessed. The mean concentration of Cr, Ni, Cu, As, Cd and Pb in studied soils were 11.56, 23.92, 37.27, 6.11, 2.01, and 17.46 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
1
8
2
Order By: Relevance
“…Geo-accumulation index (I geo ) is considered an effective tool to characterize the level of pollution from soil from the hazardous element (Proshad et al, 2018). I geo was originally introduced and defined by Muller (1969).…”
Section: Geo-accumulation Index (I Geo )mentioning
confidence: 99%
“…Geo-accumulation index (I geo ) is considered an effective tool to characterize the level of pollution from soil from the hazardous element (Proshad et al, 2018). I geo was originally introduced and defined by Muller (1969).…”
Section: Geo-accumulation Index (I Geo )mentioning
confidence: 99%
“…The second factor explains 24.10% of the total variance which includes Cd, Co, Mn and Ni. Proshad et al (2018) used the PCA method and analyzed the soil of industrial areas in Bangladesh. They divided the measured metals into three separate clusters: 1) Ni, Pb, and Cu.…”
Section: Sources Of Hms In Deposited Dustmentioning
confidence: 99%
“…It doesn't include Cr metal, which was in the moderate degree of enrichment regarding environmental protection. Proshad et al (2018) used enrichment indices to calculate contamination load in Tangail ground, located in Bangladesh. The results showed that agricultural soils were heavily contaminated with hazardous elements.…”
Section: Pollution Assessmentmentioning
confidence: 99%
“…The excessive entry of heavy metals and synthetic chemicals into the studied soils may lead to deterioration of the soil biology, thereby altering the physicochemical properties of the soil and causing other environmental problems. Increasing air, water, and soil pollution caused by traffic jams, mines, various manufacturing industries, and industrial waste is a serious problem that negatively affects public health (Islam et al 2020;Proshad et al 2018;Hani and Karimineja 2010b;Ghiyasi et al 2010b).…”
Section: Carcinogenic Risk Assessment Of Toxic Metals By Intake Of Agricultural Productsmentioning
confidence: 99%
“…(Sarkar and Paul 2016). Also, excessive entry of heavy metals and synthetic chemicals into the studied soils may lead to deterioration of the soil biology, thereby altering the physicochemical properties of the soil and causing other environmental problems (Qu et al 2012;Salama and Radwan 2005;Islam et al 2020;Proshad et al 2018;Solgi et al 2014;Solgi et al 2012;Ghasemidehkordi et al 2018a;Ghiyasi et al 2010a;Hani and Karimineja 2010a). Pruvot et al (2006) showed that the soil near the smelter is more contaminated than the reference soil.…”
Section: Introductionmentioning
confidence: 99%